Social integration, social contacts, and blood pressure dipping in African–Americans and whites - Troxel, Wendy M. (2010)
OBJECTIVE: Both the size and diversity of an individual’s social network are strongly and prospectively linked with cardiovascular morbidity and mortality. Social relationships may influence cardiovascular outcomes, at least in part, via their impact on physiologic pathways influenced by stress, such as daytime blood pressure (BP) levels. However, scant research has examined whether social relationships influence key nocturnal pathways, such as nocturnal BP dipping. METHODS: The current study examined the degree to which social integration, as measured by participants’ reported engagement in a range of different types of social relationships, and the frequency of daily social contacts influence the ratio of night/day mean arterial pressure (MAP) in a community sample of African–American and white men and women (N = 224). In addition, we examined the degree to which observed associations persisted after statistical adjustment for factors known to covary with nocturnal BP, including objective measures of sleep, catecholamines, health behaviors, and comorbidities. RESULTS: In fully adjusted models, there was a significant association between both social integration and frequency of social contacts and the ratio of night/day MAP, indicating that socially isolated individuals were more likely to have blunted nocturnal BP-dipping profiles. There was also a significant interaction between social contact frequency and ethnicity, suggesting that the benefits of social relationships were particularly evident in African–Americans. CONCLUSIONS: These findings contribute to our understanding of how social integration or conversely, social isolation, influences cardiovascular risk.